Magnetoexcitons bound to ionized-donor impurities in GaAs/AlxGa1−xAs quantum wells (2010)
The binding energy of Wannier excitons bound to ionized-donor impurities, D+, in GaAs/AlxGa1−xAs quantum-wells, is studied using the effective-mass approximation within a variational approach, as a function of the well width for different barrier heights and growth-direction applied magnetic fields. Our calculations are devoted to heavy-hole magnetoexcitons. As expected, we found that the binding energy of a heavy-hole exciton bound to a donor-ionized impurity increases with the Al concentration, as well as with the applied magnetic field. Otherwise, we found that it is higher than the corresponding for heavy-hole excitons without impurities reported by other authors. Moreover we found that the binding energy of the heavy-hole exciton bound to a donor-ionized impurity is higher (lower) for larger (smaller) quantum well width. Finally we found that our results are in very good agreement when we compare with experimental and theoretical reports.